2005
DOI: 10.1038/sj.onc.1209148
|View full text |Cite
|
Sign up to set email alerts
|

ERK activity facilitates activation of the S-phase DNA damage checkpoint by modulating ATR function

Abstract: Although Erk kinase has been recently reported to function in the DNA damage response, the mechanism governing this process is unknown. We report here that hydroxyurea (HU) activates Erk via MEK1, a process that is sensitized by a constitutively active MEK1 (MEK1Q56P) and attenuated by a dominant-negative MEK1 (MEK1K97M). While ectopic MEK1Q56P sensitized HU-induced S-phase arrest, inhibition of Erk activation via U0126, PD98059, and MEK1K97M attenuated the arrest, and thereby enhanced cells to HU-induced toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 49 publications
1
52
0
Order By: Relevance
“…Etoposide-induced ERK activation was shown to mediate cell cycle arrest in an ATM-dependent but p53-independent manner (47). In the case of other stresses, such as hydroxyurea and ionizing radiation, ERK activation was required for S phase and G 2 /M checkpoint arrest, respectively (48,49). Moreover, Yan et al reported that ionizing radiation-induced ERK1/2 activation required a direct interaction with BRCA1 for G 2 /M cell cycle checkpoint arrest (50).…”
Section: Discussionmentioning
confidence: 99%
“…Etoposide-induced ERK activation was shown to mediate cell cycle arrest in an ATM-dependent but p53-independent manner (47). In the case of other stresses, such as hydroxyurea and ionizing radiation, ERK activation was required for S phase and G 2 /M checkpoint arrest, respectively (48,49). Moreover, Yan et al reported that ionizing radiation-induced ERK1/2 activation required a direct interaction with BRCA1 for G 2 /M cell cycle checkpoint arrest (50).…”
Section: Discussionmentioning
confidence: 99%
“…break formation in the S phase (47). A similar mechanism could link ERK and ATM perhaps through a feedback loop that might regulate cellular homeostasis and sense the well being of the cell; if DNA damage is repairable, prosurvival ERK signaling might positively influence HRR, whereas overwhelming DNA damage might inhibit ERK signaling and HRR.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, CDK1 is unlikely to be required to phosphorylate Ser5 when cells are arrested in S phase because it is only active in the G2/M phase of the cell cycle (Clute and Pines 1999). More likely, either ERK or DNA-PK modifies RNAPII Ser5 after HU, as both kinases have been shown to be activated by S-phase block (Wu et al 2006). Further Figure 8.…”
Section: Discussionmentioning
confidence: 99%